2022
DOI: 10.2174/1871530322666220110161458
|View full text |Cite
|
Sign up to set email alerts
|

Cortex Mori Radicis Attenuates Streptozotocin-induced Diabetic Renal Injury in Mice via Regulation of Transient Receptor Potential Canonical Channel 6

Abstract: Objective: Cortex Mori Radicis (CMR) has been reported to possess anti-pyretic, anti-convulsant, anti-allergic, anti-inflammatory, and anti-diabetic effects. In this study, we aimed to investigate the effect of CMR on streptozotocin (STZ)-induced diabetic renal injury in mice and explore the underlying mechanism. Methods: Mice were gavaged with different doses of CMR for continuous 7 days. Then, STZ (50 mg/kg) was applied to induce renal injury associated with type 1 diabetes. Firstly, blood glucose levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Focal glomerulosclerosis caused by mutations in the TRPC6 gene has been a hot research topic over the years [8,9].Since 2005, when winn et al [10] first cloned the TRPC6 gene that causes FSGS from patients with familial focal segmental glomerulosclerosis (FSGS), the TRPC6 gene and the TRPC6 cation channel protein have been continuously research [11].There are interactions between TRPC6 cation channel proteins and the cleavage septum molecules Nephrin and Podocin, which are jointly involved in physiological functions such as intercellular signaling between podocytes, cell polarization, and stabilization of the cytoskeleton [10].In 2018, scholars Chen Lei et al [12] observed by cryo-electron microscopy that TRPC6 consists of amino acids that are folded into two long helices, namely CH1 and CH2.CH1 runs from the periphery to the center of the channel and connects to CH2 through a 90° turn.And it was seen that TRPC6 protein is a 6-transmembrane protein consisting of 931 amino acids, with a small pore region between the 5th and 6th transmembrane proteins, which forms the cation channel.Wang Q et al [13] stated that in damaged podocytes, TRPC6 protein regulates cation channels through the Rho/ROCK dependent pathway regulates foot cell actin stress fiber formation and focal adhesions. New studies demonstrated that nephrin and TRPC6 proteins have direct or indirect interactions in podocytes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Focal glomerulosclerosis caused by mutations in the TRPC6 gene has been a hot research topic over the years [8,9].Since 2005, when winn et al [10] first cloned the TRPC6 gene that causes FSGS from patients with familial focal segmental glomerulosclerosis (FSGS), the TRPC6 gene and the TRPC6 cation channel protein have been continuously research [11].There are interactions between TRPC6 cation channel proteins and the cleavage septum molecules Nephrin and Podocin, which are jointly involved in physiological functions such as intercellular signaling between podocytes, cell polarization, and stabilization of the cytoskeleton [10].In 2018, scholars Chen Lei et al [12] observed by cryo-electron microscopy that TRPC6 consists of amino acids that are folded into two long helices, namely CH1 and CH2.CH1 runs from the periphery to the center of the channel and connects to CH2 through a 90° turn.And it was seen that TRPC6 protein is a 6-transmembrane protein consisting of 931 amino acids, with a small pore region between the 5th and 6th transmembrane proteins, which forms the cation channel.Wang Q et al [13] stated that in damaged podocytes, TRPC6 protein regulates cation channels through the Rho/ROCK dependent pathway regulates foot cell actin stress fiber formation and focal adhesions. New studies demonstrated that nephrin and TRPC6 proteins have direct or indirect interactions in podocytes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we constructed a COPD rat model and investigated the effects of SJQJD on the pulmonary microbiota of COPD rats through 16S rRNA sequencing. Modern pharmacology indicates that the extract of mori cortex has a regulatory effect on oxidative stress ( Zhai et al., 2022 ), chrysanthemi indici flos, trichosanthis pericarpium, pheretima, fritillariae cirrhosae bulbus, phragmitis rhizoma all exhibit anti-inflammatory activity ( Park et al., 2016 ; Liu et al., 2020 ; Tian et al., 2020 ; Li et al., 2022 ; Liu et al., 2024 ), plantaginis semen has the function of regulating lipid metabolism and immune response ( Sun et al., 2019 ; Ren et al., 2021 ), glycyrrhizae radix et rhizoma has anti-inflammatory and detoxifying effects ( Li et al., 2019 ; Jiang et al., 2022 ). These physiological processes are involved in various stages of physiological pathology.…”
Section: Introductionmentioning
confidence: 99%